Neurosteroid allopregnanolone inhibits glutamate release from rat cerebrocortical nerve terminals. Issue 3 (3rd November 2018) - Chang, Yi; Hsieh, Hsi Lung; Huang, Shu Kuei; Wang, Su Jane
Abstract: Allopregnanolone, an active metabolite of progesterone, has been reported to exhibit neuroprotective activity in several preclinical models. Considering that the excitotoxicity caused by excessive glutamate is implicated in many brain disorders, the effect of allopregnanolone on glutamate release in rat cerebrocortical nerve terminals and possible underlying mechanism were investigated. We observed that allopregnanolone inhibited 4‐aminopyridine (4‐AP)‐evoked glutamate release, and this inhibition was prevented by chelating the extracellular Ca 2+ ions and the vesicular transporter inhibitor. Allopregnanolone reduced the elevation of 4‐AP‐evoked intrasynaptosomal Ca 2+ levels, but did not affect the synaptosomal membrane potential. In the presence of N‐, P/Q‐, and R‐type channel blockers, allopregnanolone‐mediated inhibition of 4‐AP‐evoked glutamate release was markedly reduced; however, the intracellular Ca 2+ ‐release inhibitors did not affect the allopregnanolone effect. Furthermore, allopregnanolone‐mediated inhibition of 4‐AP‐evoked glutamate release was completely abolished in the synaptosomes pretreated with inhibitors of Ca 2+ /calmodulin, adenylate cyclase, and protein kinase A (PKA), namely calmidazolium, MDL12330A, and H89, respectively. Additionally, the allopregnanolone effect on evoked glutamate release was antagonized by the GABAA receptor antagonist SR95531. Our data are the first to suggest that allopregnanolone reduce the Ca 2+ influx through N‐, P/Q‐, and R‐type Ca 2+ channels, through the activation of GABAA receptors present on cerebrocortical nerve terminals, subsequently suppressing the Ca 2+ ‐calmodulin/PKA cascade and decreasing 4‐AP‐evoked glutamate release. Abstract : Allopregnanolone may act at GABAA receptors present on cerebrocortical nerve terminals to decrease the Ca 2+ influx through N‐ and P/Q‐type Ca 2+ channels, which subsequently reduces the Ca 2+ ‐calmodulin/AC/cAMP/PKA cascade to cause a decrease in glutamate release.